"A Game-Theoretic Analysis of Childhood Vaccination Behavior: Nash versus Kant" - Philippe De Donder; Humberto Llavador; Stefan Penczynski; John E. Roemer; Roberto Vélez (Center for Economic Studies and ifo Institute (CESifo), 2022)
Whether or not to vaccinate one's child is a decision that a parent may approach in several ways. The vaccination game, in which parents must choose whether to vaccinate a child against a disease, is one with positive externalities (herd immunity). In some societies, not vaccinating is an increasingly prevalent behavior, due to deleterious side effects that parents believe may accompany vaccination. The standard game-theoretic approach assumes that parents make decisions according to the Nash behavioral protocol, which is individualistic and non-cooperative. Because of the positive externality that each child's vaccination generates for others, the Nash equilibrium suffers from a free-rider problem. However, in more solidaristic societies, parents may behave cooperatively –they may optimize according to the Kantian protocol, in which the equilibrium is efficient. We test, on a sample of six countries, whether childhood vaccination behavior conforms better to the individualistic or cooperative protocol. In order to do so, we conduct surveys of parents in these countries, to ascertain the distribution of beliefs concerning the subjective probability and severity of deleterious side effects of vaccination. We show that in all the countries of our sample the Kant model dominates the Nash model. We conjecture that, due to the free-rider problem inherent in the Nash equilibrium, a social norm has evolved, quite generally, inducing parents to vaccinate with higher probability than they would in the non-cooperative solution. Kantian equilibrium offers one precise version of such a social norm.
Keywords: C72; D62; D63; I12; 330; Kantian equilibrium; Nash equilibrium; vaccination; social norm